2019
DOI: 10.1007/s10880-019-09611-9
|View full text |Cite
|
Sign up to set email alerts
|

The Physician’s Tears: Experiences and Attitudes of Crying Among Physicians and Medical Interns

Abstract: We examined several aspects of the crying experiences of physicians and medical interns, including the most common reasons to cry in the workplace, and their perceptions of and attitudes towards crying in the workplace and in the presence of a patient. A sample of Dutch physicians and medical interns (Nphysicians = 1068 and Nmedical interns = 302 and for the full version Nphysicians = 776 and Nmedical interns = 181) completed an especially designed anonymous online questionnaire about experiences with crying i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…An illustrative example of such a context is the work setting. Studies show that crying at work may be considered inappropriate and associated with negative evaluation of the crier in terms of competence and competence-related characteristics (Elsbach & Bechky, 2018; Fischer et al, 2013; Janssens et al, 2019). For instance, Elsbach and Bechky (2018) demonstrated that women crying in professional work settings were perceived as emotionally unstable and unprofessional because they were expected to suppress their emotions and refrain from behaviors that may interfere with work.…”
Section: Situational Valence and Perceived Appropriatenessmentioning
confidence: 99%
“…An illustrative example of such a context is the work setting. Studies show that crying at work may be considered inappropriate and associated with negative evaluation of the crier in terms of competence and competence-related characteristics (Elsbach & Bechky, 2018; Fischer et al, 2013; Janssens et al, 2019). For instance, Elsbach and Bechky (2018) demonstrated that women crying in professional work settings were perceived as emotionally unstable and unprofessional because they were expected to suppress their emotions and refrain from behaviors that may interfere with work.…”
Section: Situational Valence and Perceived Appropriatenessmentioning
confidence: 99%
“…Furthermore, crying can be a powerful way for doctors to connect with their patients and demonstrate empathy. Patients and their families often appreciate a doctor who is willing to share and thus validate their emotions [1,3]. By allowing doctors to cry, we can improve the doctor-patient relationship and ultimately improve the quality of care that patients receive.…”
Section: Notementioning
confidence: 99%
“…Doctors are expected to maintain a level of professionalism and control in their interactions with patients. Crying may be seen as a sign of weakness or lack of professionalism, which could erode the trust and confidence that patients have in their doctors [2,3].…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…In the therapeutic setting, it is not only the patients who cry. Indeed, tears are also not uncommon among therapists and other health professionals (Blume-Marcovici et al, 2017; Janssens, Sweerts, & Vingerhoets, 2019). For example, ’t Lam and colleagues (2018) reported that as many as 87.4% of their large sample of over 800 mental health providers endorsed having cried at least once during a therapy session (with many likely crying more than once), with no significant difference between male and female therapists.…”
Section: Tears In the Clinical Settingmentioning
confidence: 99%